(untitled) (Педагогіка вищої та середньої школи, 2009)
In the article rasmatrivaetsya problem of application of plastic anatomy in complex study to the formoobrazovatel’nogo process of studentami - trudovikami on employments of fine art. It is rotined that forming of graphic skills and abilities considerably depends on knowledges the students of plastic anatomy.